2020
DOI: 10.31254/jahm.2020.6213
|View full text |Cite
|
Sign up to set email alerts
|

Bauhinia purpurea: An Updated Pharmacological Profile

Abstract: Bauhinia purpurea (B. purpurea) (family: Fabaceae) commonly called as butter fly tree has vast medicinal uses and remarkable pharmacological potential. Various phytoconstituents, extracts and parts of this plant were possess significant pharmacological activities such as cardiac activity, antifungal, wound healing, antidiabetic, antiulcer, antioxidant, antinociceptive, hepatoprotective, nephroprotective, antidiarrhoeal, anti-inflammatory, antipyretic, analgesic, antimalarial, gastro protective and cytoprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This genus included 300 species of trees or shrubs widely spread in hot and intermediate climatic areas of the world 1, 2 . Many of its species possess various pharmacological and therapeutic actions such as anti-inflammatory, anti-diabetic, antitumor, antimicrobial, hepatoprotective, and anti-ulcer activities 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This genus included 300 species of trees or shrubs widely spread in hot and intermediate climatic areas of the world 1, 2 . Many of its species possess various pharmacological and therapeutic actions such as anti-inflammatory, anti-diabetic, antitumor, antimicrobial, hepatoprotective, and anti-ulcer activities 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Bauhinia purpurea L. (B. purpurea) is a small tropical evergreen tree or erect shrub grows up to 17 m tall. It is native to China and India and is indigenous to Southern Asia and widely distributed throughout the world 5 Phytochemical studies on this species reported the existence of several secondary metabolites as saponins, flavonoids, phenolic compounds, triterpenoids, fatty acids, phytosterols, and alkaloids 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst them is Bauhinia purpurea (B. purpurea) which is a well known plant with versatile therapeutic potential. Bauhinia purpurea is one of the plants that has gained interest among researchers as a potential new source of medicinal agents 13 . Orchid tree, Bauhinia purpurea, is a tropical evergreen small tree or shrub up to 4-10 m tall and 2m across.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Bauhinia, family Leguminosae (Subfamily: Caesalpinioideae), consists 300 species all over the world where around 15 species reported in India as tree, shrubs or few as climber 3 . It is indigenous to South China and India but naturally distributed in Nepal, Bhutan, Pakistan, Shri Lanka, Myanmar and Thailand also.…”
mentioning
confidence: 99%